Localization of Contextual and Context Removed Auditory Fear Memory within the Basolateral Amygdala Complex. (1st February 2019) - Chaaya, N.; Jacques, A.; Belmer, A.; Richard, D.J.; Bartlett, S.E.; Battle, A.R.; Johnson, L.R.
Highlights: Contextual fear conditioning leads to an increase of Arc and c-Fos in the amygdala. Arc and c-Fos patterns differ when contextual fear conditioning is altered by a tone. Adjusted auditory fear memories are less strongly represented in amygdala. Abstract: Debilitating and persistent fear memories can rapidly form in humans following exposure to traumatic events. Fear memories can also be generated and studied in animals via Pavlovian fear conditioning. The current study was designed to evaluate basolateral amygdala complex (BLC) involvement following the formation of different fear memories (two contextual fear memories and one adjusted auditory fear memory). Fear memories were created in the same context with five 1.0 mA (0.50 s) foot-shocks and, where necessary, five auditory tones (5 kHz, 75 dB, 20 s). The adjusted auditory fear conditioning protocol was employed to remove background contextual fear and produce isolated auditory fear memories. Immunofluorescent labeling was utilized to identify neurons expressing immediate early genes (IEGs). We found the two contextual fear conditioning (CFC) procedures to produce similar levels of fear-related freezing to context. Contextual fear memories produced increases in BLC IEG expression with distinct and separate patterns of expression. These data suggest contextual fear memories created in slightly altered contexts, can produce unique patterns of amygdala activation. The adjusted auditory fear conditioning procedure produced memories to a tone, but not to a context. This group, where no contextual fear was present, had a significant reduction in BLC IEG expression. These data suggest background contextual fear memories, created in standard auditory fear conditioning protocols, contribute significantly to increases in amygdala activation.